Tonsillar transcriptional profiles in atopic and non-atopic subjects - Hanif Tanzeela; Ivaska Lotta E; Ahmad Freed; Tan Ge; Mikola Emilia; Puhakka Tuomo; Palomares Oscar; Akdis Cezmi A; Toppila-Salmi Sanna; Jartti Tuomas (WILEY, 2022)
Background
Emerging research suggests that local lymphatic tissue such as tonsils have important role in regulating the immune responses. However, allergen sensitization-induced alterations in transcriptome of tonsils are not known.
Objectives
To examine the key differences in tonsillar gene expression between atopic and non-atopic subjects and further by type of sensitization.
Methods
RNA-sequencing was performed on 52 tonsillar samples from atopic and non-atopic tonsillectomy patients. Sensitization to common food- and aero-allergen was defined by allergen specific IgE. Following groups were studied: (1) aero- and food-allergen sensitized (AS+FS) versus non-sensitized (NS), (2) aeroallergen-sensitized (AS) versus food-allergen sensitized (FS), (3) AS versus NS, (4) FS versus NS. Bioinformatics analysis was done using DESeq2(v3.10.2), WGCNA and GATK pipeline in R software (v3.3.1). Protein-protein interaction network was made from String database.
Results
We studied 13 aeroallergen-sensitized, 6 food-allergen sensitized, 4 both food-and aero-allergen-sensitized and 29 non-sensitized tonsillectomy patients. Overall, 697 unique differentially expressed genes (DEGs) were detected in all sensitized subgroups including chemokines (CXCL2, CXCL8, CXCL10, CXCL11), IL-20RA, MUC1 and MUC20. When comparing different groups, the gene expression profiles overlapped except the AS versus FS group comparison, suggesting significantly different gene expression between the two sensitization subgroups. Furthermore, aeroallergen-sensitized subjects had more prominent immune responses compared with non-sensitized and food-allergen sensitized subjects including gene expression for IL-17 pathway and Toll-like receptor signalling pathway.
Conclusion
Allergic sensitization is associated with extensive tonsillar transcriptomic alterations and changes in immune related genes and pathways. Distinct differences were found between aero-allergen and food-allergen sensitization.